2015
DOI: 10.17221/8417-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a cypermethrin-based pesticide on early life stages of common carp (Cyprinus carpio L.)

Abstract: ABSTRACT:The aim of this study was to assess the effects of Cyperkill 25 EC (a.i. cypermethrin 250 g/l) on cumulative mortality, growth indices, and ontogenetic development of embryos and larvae of common carp (Cyprinus carpio L.). An early-life stage toxicity test was used. Liver, intestine, kidneys, and gills of surviving larvae were examined, and the activity of the detoxifying and antioxidative enzymes glutathione reductase (GR), glutathione peroxidase (GPx), catalase (CAT), glutathione-S-transferase (GST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Interestingly, in this study we also found a significant reduction in body length of DP exposed common carps. These results are similar with those that reported reduction of fish growth upon exposure to other chemicals, for example organophosphate insecticides and pyrethroid insecticides (Allison, 1977;Machova et al, 2010;Richterova et al, 2015;Werner and Moran, 2008). In the present study, changes in the developmental malformation of common carp larvae may be due to DP exposure induced DNA damage (single/double strand breaks) and oxidative stress.…”
Section: Relationship Between Comet Assay and Morphological Abnormalitysupporting
confidence: 92%
“…Interestingly, in this study we also found a significant reduction in body length of DP exposed common carps. These results are similar with those that reported reduction of fish growth upon exposure to other chemicals, for example organophosphate insecticides and pyrethroid insecticides (Allison, 1977;Machova et al, 2010;Richterova et al, 2015;Werner and Moran, 2008). In the present study, changes in the developmental malformation of common carp larvae may be due to DP exposure induced DNA damage (single/double strand breaks) and oxidative stress.…”
Section: Relationship Between Comet Assay and Morphological Abnormalitysupporting
confidence: 92%
“…These findings could be attributed to the metabolic changes in protein and carbohydrate metabolism of fish induced by toxic stress, which led to the consumption of energy storage to detoxify the toxicant or repair mechanisms; hence, little energy was available for growth. A reduction in growth has previously been reported for LCT exposed in O. niloticus [ 30 ]; likewise for cypermethrin (a member of pyrethroids family) given to common carp [ 50 ], and MTM given to Hoplobatrachus rugulosus [ 25 ].…”
Section: Discussionmentioning
confidence: 88%
“…A similar developmental study conducted on the common carp (Cyprinus carpio L.) embryos also indicated that CN exposure has led to growth retardations and embryonic death. In these embryos the estimated antioxidant enzymes (glutathione-S-transferase, glutathione reductase, and glutathione peroxidase) activities were significantly lowered than the control group embryos (Richterova et al, 2015). Thus, it seems customary to believe that the oxidative stress induced by CN exposure must play a pivotal role in embryonic developmental disruptions (Huang et al, 2016;Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 93%